The audiovisual evidence collected during police stops: Legality of military police actions in light of Custody Hearings (Research, Society and Development, 2025)
The actions of the Military Police during stops are constantly evaluated through the lens of legality, particularly in the context of custody hearings, where potential abuses of authority are examined. In this context, audiovisual recordings obtained at the moment of police intervention emerge as tools aimed at ensuring transparency and protecting fundamental rights. This study aimed to analyze the relevance and effectiveness of audiovisual informational elements collected during police stops, focusing on their use in custody hearings. The research was an applied study with a qualitative-quantitative and descriptive-exploratory approach. The methodology involved a literature and document review, consultations with experts, and the administration of questionnaires to volunteers from the Military Police of Alagoas (PMAL). The results indicate that most officers recognize the evidentiary potential of audiovisual recordings, although some skepticism remains regarding their effective use by the judiciary. It was also found that, despite agreement on the usefulness of the recordings, some officers believe that producing such evidence may compromise the operational effectiveness of the team during the stop. Consultations with judges confirmed the importance of audiovisual records in verifying the legality of police actions, though they emphasized the need for clear regulations to prevent misuse of the footage. The study concludes that, although practical and legal challenges persist, the systematic adoption of audiovisual technologies can strengthen the legality of police procedures and ensure greater balance during custody hearings.